IMPLEMENTATION OF OPEN INQUIRY AND GUIDED INQUIRY LEARNING MODELS TOWARD THE JUNIOR HIGH SCHOOL STUDENTS COLLABORATIVE ATTITUDE - Suryani, Dwi Indah (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract The aim of this study is to find out enhancement difference of collaborative  attitude of students using Open Inquiry learning model and Guided Inquiry in Temperature and Alteration theme. Sample of study are 56 students grade VII students of Junior High School in Palembang City.  This study use quasi experiment method.  Data collection technique is by attitude scale. Data analysis technique use IBM SPSS Statistics 22 program.  The result of study analysis show that collaborative attitude in Open Inquiry class is 84.5% with good category and in Guided Inquiry class is 85.0% with good category. Based on result of difference test, it can be concluded that there is no difference in collaborative attitude of students who use Open Inquiry learning model and Guided Inquiry learning model. Keywords: Open Inquiry, Guided Inquiry, Collaborative Attitude, Temperature and Alteration.